Ramadan fasting in health and disease (2019): A narrative review - Ali, Khawla; Abdulla, Sara; Badi, Amal; Hafidh, Khadija; Beshyah, Salem (Ibnosina Journal of Medicine and Biomedical Sciences, 2020)
Introduction: Literature on the health aspects of Ramadan fasting (RF) is widespread in many journals, making it less readily available to those interested in the subject. Materials and Methods: This is a narrative, nonsystematic review of international literature from two major online databases (viz., Scopus and PubMed) in 1 year (2019). The search term “RF” was used, and relevant literature was narrated in a concise thematic account excluding diabetes. Results: The publications spanned the fundamental, clinical, ethical, professional, cultural, and advocacy facets of the subject. The publications crossed the conventional disciplinary lines and geographical locations and appeared in journals with different access systems. The content is presented under relevant themes depending on the available literature. Basic coverage included changes in physiology, nutrition, and metabolism during Ramadan. Clinical aspects such as the impact of RF on kidney function, pregnancy outcome, fetal life, structure and function of eyes, and athletes' well-being received comparatively prominent coverage by researchers in 2019. Gut, liver, skin, skeleton, and blood were also covered. Other workers focused on documenting the perception, attitudes, and practices of both patients and health-care professionals during Ramadan. Conclusions: The health aspects of RF received sustained academic interest with a wide spectrum in 2019. We provided a scoping overview to help researchers and clinicians catch up quickly with the state-of-the-art today.
Keywords: Bibliometric; diabetes; literature; patients' perceptions; pregnancy; professional; Ramadan; research; sports medicine